The Association Between Diabetes Mellitus With a Five-year Survival Rate of Breast Cancer Patients - Marjan Sharifi Nasab; Hamideh Yazdimoghaddam; Seyedeh Tahereh Mohaddes; Mohammad Hasan Rakhshani; Kazem Abbaszadeh Goudarzi (Gonabad University of Medical Sciences, 2022)
Background: Breast cancer is a highly prevalent malignancy leading to death across the world. However, patient survival is greatly affected by making a diabetes diagnosis. The present assessed the association between diabetes mellitus and the five-year survival rate of breast cancer patients at the cancer treatment centers. Methods: This retrospective follow‐up study was conducted on 534 diabetic women with breast cancer who had been diagnosed during 1999-2013 referring to cancer treatment centers of Mashhad University of Medical Sciences. Demographic and clinical data of patients were collected through questionnaires in these centers searching the patient's available medical files. Notably, the patients were selected via systematic random sampling, and also the five-year survival of the patients was assessed during the follow-up period up to 2018. Results: In breast cancer patients, the diabetes prevalence was 12.7%. Of note, the mean and median five-year survival were 9.95 and 13, respectively. No significant difference was observed in the survival rate of the diabetic and non-diabetic patients (95% CI: 0.431-1.334; hazard ratio [HR]: 0.758; P=0.34). The survival time increased in the patients receiving metformin as a treatment protocol (95% CI: 0.226-0.950; HR: 0.5; P=0.04). Conclusion: Based on the results, training diabetic patients regarding risk factors of breast cancer and effective therapies in controlling hyperglycemia that need to screen in the early diagnosis of breast cancer are essential to improve health and increase survival rate in diabetic patients.